Clinical trial to evaluate the outcome of canal wall up and canal wall down tympanomastoidectomy (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the hearing outcomes of chronic suppurative otitis media surgery. Chronic suppurative otitis media (CSOM) surgery composed of two procedure; canal wall up mastoidectomy (CWU) and canal wall down mastoidectomy (CWD).Material and Methods:The study included 29 patients with CSOM diagnosis and patients a mean age of 37.02 ± 2.4 years (y). The demographic features (age, gender), clinical features and intraoperative findings of the patients were recorded. Patients’ hearing was evaluated with pure tone audiometry (PTA) at 0.5, 1, 2, 4 and 8 kHz and pre-postoperative air bone gap (ABG) difference. Pre- and post-operative air-bone gap (ABG) at 12 months after ossiculoplasty. There were 8 patients who underwent CWD and 21 patients who underwent CWU.Results: TWhen preoperative and postoperative ABG for the patients are compared, there were statistically significant differences identified at 0.5, 1, 2 and 8 kHz. However, there was no statistically significant difference identified at 4 kHz.Conclusion: Regardless to the surgical technique, statistically significant levels of hearing gain were provided at 0.5, 1, 2 and 8 kHz; however, there was no hearing gain at 4 kHz after the surgical procedure.